Characterization of Catalyst by Temperature-Programmed Technique - อัศวสุขี อาทิตย์ (KKU Science Journal, 2014)
Although the catalyst has been studied for over 20 years, the understanding of the altering of catalyst during the reaction and also preparation are rather limited. It has been shown that different catalytic activities and the reaction pathway, and hence product selectivity are pronounced when different catalysts are introduced. The temperature-programmed technique can be used a potentially tool in order to study the characteristic and catalytic activity. The temperature-programmed technique including temperature-programmed desorption (TPD), temperature-programmed desorption of adsorbed i-propylamine (IPA-TPD), temperatureprogrammed reduction (TPR), temperature-programmed reaction (TPRx), temperatureprogrammed hydrogen evolution (TPHE), temperature-programmed oxidation (TPO), and temperature-programmed sulfidation (TPS) are focused on this article.